Impact of social reintegration activities on the detainee's behavior according to age, length of detention and recidivism Impactul activităților de reintegrare socială asupra comportamentului deținutului în funcție de vârstă, durata detenției și recidivă - POPA Ecaterina (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
This article brings to the fore the importance of detainees ’participation in social reintegration programs for behavior change. It is also considered to determine a correlation between the personality traits of detainees and age, length of detention and recidivism. Thus, the statistical results obtained by the Anova test and the Pearson correlation test are consistent with other similar studies, which highlight the personality traits of adult detainees such as M. Bulten and S. Maruna, but also with studies that observed the types of coping at the level of detainees with different personality patterns made by J. L. Ireland and C. L. Power.